Application of PS-ADI-MRTD Method in Frequency Selective Surface Analysis - Yawen Liu; Pin Zhang (Applied Computational Electromagnetics Society Journal (ACES), 2020)
In this paper, a novel periodic spectral alternating direction implicit multi-resolution time domain (PS-ADI-MRTD) method is proposed for solving periodic structures. The algorithm for inversion of the block periodic tri-diagonal matrices is presented. A typical example is given to validate the effectiveness of the proposed algorithm, and the numerical results also show that the proposed algorithm can save more computation time than the traditional MRTD method. Furthermore, the PS-ADI-MRTD method is applied to analyze the electromagnetic scattering characteristics of two types frequency selective surface (FSS) structures.